Increased CTLA-4+ T cells may contribute to impaired T helper type 1 immune responses in patients with chronic obstructive pulmonary disease - Tan, D.; Teo, T.; Setiawan, A.; Ong, N.; Zimmermann, M.; Price, Patricia; Kirkham, L.; Moodley, Y. (2017)
Impaired T helper type 1 (Th1) function is implicated in the susceptibility of patients with chronic obstructive pulmonary disease (COPD) to respiratory infections, which are common causes of acute exacerbations of COPD (AECOPD). To understand the underlying mechanisms, we assessed regulatory T (Treg) cells and the expression of an inhibitory T-cell receptor, cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4). Cryopreserved peripheral blood mononuclear cells (PBMC) from patients with AECOPD (n = 17), patients with stable COPD (sCOPD; n = 24) and age-matched healthy non-smoking controls (n = 26) were cultured for 24 hr with brefeldin-A or monensin to detect intracellular or surface CTLA-4 (respectively) by flow cytometry. T cells in PBMC from AECOPD (n = 9), sCOPD (n = 14) and controls (n = 12) were stimulated with anti-CD3 with and without anti-CTLA-4 blocking antibodies and cytokines were quantified by ELISA. Frequencies of circulating T cells expressing intracellular CTLA-4 were higher in sCOPD (P = 0·01), whereas patients with AECOPD had more T cells expressing surface CTLA-4 than healthy controls (P = 0·03). Increased frequencies of surface CTLA-4 + CD4 + T cells and CTLA-4 + Treg cells paralleled increases in plasma soluble tumour necrosis factor receptor-1 levels (r = 0·32, P = 0·01 and r = 0·29, P = 0·02, respectively) in all subjects. Interferon-? responses to anti-CD3 stimulation were inversely proportional to frequencies of CD4 + T cells expressing intracellular CTLA-4 (r = -0·43, P = 0·01). Moreover, CTLA-4 blockade increased the induction of interferon-?, tumour necrosis factor-a and interleukin-6 in PBMC stimulated with anti-CD3. Overall, chronic inflammation may expand sub-populations of T cells expressing CTLA-4 in COPD patients and therefore impair T-cell function. CTLA-4 blockade may restore Th1 function in patients with COPD and so aid the clearance of bacterial pathogens responsible for AECOPD.